The Training and Evaluation of the “Dual-Index” Screening Method for Neonatal Congenital Heart Disease: A Multi-Center Study in China - Panpan Huang; Qing Gu; Xiaoting Zhu; Ijaz ul Haq; Liling Li; Xiaojing Hu; Guoying Huang (International Journal of Neonatal Screening)
Background: This study aimed to enhance the scope of neonatal congenital heart disease (CHD) screening by evaluating the effectiveness of training personnel in CHD screening using the “dual-index” method, combining pulse oximetry with cardiac murmur auscultation. Methods: From 2019 to 2022, a total of 2374 screening personnel from the Xinjiang, Yunnan, Hainan, Fujian, and Anhui provinces underwent training in neonatal CHD screening using the “dual-index” method, which involves pulse oximetry and cardiac murmur auscultation. Pre- and post-training assessments were conducted using a neonatal CHD screening knowledge questionnaire, distributed through the Questionnaire Star platform, to evaluate the impact of the training. The annual neonatal CHD screening rates were consistently recorded in these five provinces during the same period to assess the increase in screening coverage. Results: After the training, the screening personnel exhibited a significantly improved understanding of the neonatal CHD screening method (p < 0.001). Additionally, the professional background (t = −8.007, p < 0.001) and years of experience (t = 2.839, p = 0.005) of the screening personnel were identified as independent factors influencing their screening knowledge. During the same period, there was consistent linear growth in the screening coverage rate for neonatal CHD across the five provinces (χ2 = 121065.416, p < 0.001). Conclusion: Standardized training in the “dual-index” method, incorporating pulse oximetry and cardiac murmur auscultation, for screening personnel significantly enhances their screening knowledge, thereby playing a critical role in expanding the coverage of neonatal CHD screening.